Valorization of Fenton sludge by pyrolysis as a green adsorbent for arsenate removal - Cho, Eun Ji; Kyu-Kang, Jin; Lee, Chang Gu; Park, Seong Jik (Applied Organometallic Chemistry, 2024)
Significant quantities of Fenton sludge (FS) are produced during the treatment of industrial wastewater from the plating industry because of the removal of residual organic matter and color-causing substances. This study proposes repurposing waste FS as a valuable resource to contribute to environmentally favorable remediation initiatives. This study focuses on producing Fenton sludge biochar (FS-BC), which effectively removes As(V) from wastewater and offers a sustainable solution for wastewater treatment. Different FS-BC samples were produced at various pyrolysis temperatures (300–900 °C), with FS-BC-900 exhibiting the greatest As(V) adsorption capacity. As(V) removal was primarily mediated by electrostatic attraction with iron oxide, and adsorption via inner-sphere complex formation, as revealed by the XPS analysis. FS-BC-900 had a remarkable maximum As(V) adsorption capacity of 148.7 mg/g (initial concentration: 100–900 mg/l; reaction time: 96 h; pH 7.86), surpassing many other adsorbents reported in the literature. FS-BC-900 also demonstrated a high As(V) removal percentage, with 6.67 g/l of FS-BC-900 removing 96.8% of the As(V). Notably, the adsorption of As(V) by FS-BC-900 was affected by certain factors, including pH and carbonate presence. High pH and carbonate inhibited the ability of FS-BC-900 to adsorb As(V). This study presents a novel method for utilizing FS to combat As(V)-contaminated water-induced environmental contamination. This study contributes to eco-friendly and sustainable wastewater treatment and As(V) remediation strategies by transforming waste into valuable resources.
Keywords: Adsorption capacities; Arsenate removal; Biochar; Fenton sludge; Industrial wastewaters; Plating industry; Repurposing; Sustainable solution; Thermal activation; Valorisation; arsenate removal; biochar; Fenton sludge; iron oxide; thermal activation